Effect of Flecainide on Multifocal Ectopic Purkinje-Related Premature Contractions in an R814W SCN5A Carrier - Hisham Ahamed, MD, DM; Arun Gopi, MD, DM (JACC: Case Reports, 2024)
Multifocal ectopic Purkinje-related premature contraction (MEPPC) is an autosomal dominant SCN5A channelopathy characterized by frequent multiform premature ventricular contractions originating from the His-Purkinje system. We present a patient with an MEPPC phenotype whose genetic testing identified a pathogenic SCN5A (HGNC:10593) variant amenable to precision antiarrhythmic therapy with flecainide.